Adsorption of uranyl ion on acid-modified zeolitic mineral clinoptilolite - Matijašević Srđan D.; Daković Aleksandra S.; Ileš Deana A.; Milićević Sonja Z. (Hemijska Industrija, 2009)
In this paper, the results of adsorption of uranyl ion on acid-modified zeolitic mineral clinoptilolite are presented. Adsorption was investigated at different amounts of solid phase in suspension, as well as at different pH values. The modified clinoptilolite samples were obtained by treatment of clinoptilolite with acids: hydrochloric, oxalyc and citric. Starting and modified clinoptilolites were characterized by chemical analysis, thermal (DT/TG) analysis and by determination of cation exchange capacity, while starting and nonadsorbed amounts of uranyl ion were determined by fluorometric method. Uranyl ion adsorption experiments on natural unmodified zeolitic mineral showed that uranyl ion adsorption was low (29.2%) and that treatment of clinoptilolite with acids significantly increases the adsorption of uranyl ion (>90%). In the case of acid treated clinoptilolites, the highest adsorption of uranyl ion was achieved on clinoptilolite modified with hydrochloric acid. Kinetics of adsorption showed that adsorption of uranyl ion begins very fast and that the most of uranyl ion was adsorbed in first 30 min. Practically, there were no changes in uranyl ion adsorption within next 72 h.